Analysis of Level Practice Satisfaction on Basic Chemical Laboratory Performance Faculty of MIPA Jenderal Soedirman University - Anggraeni, Diah Ratna; Azizah, Nailatul (Proceeding International Conference on Science and Engineering, 2020)
Education is an important aspect of life. In the context of providing education, it is necessary to have adequate human resources and supporting facilities. The level of performance of officers from each facility must also be considered in order to create the desired learning conditions. To find out the level of performance of the services provided in accordance with what is desired or not is to conduct a survey of facility users regarding all aspects of the facility. Therefore, the authors use the Partial Least Square method to analyze the influence of human resource factors and facilities and infrastructure on the satisfaction of the students at the Laboratory of the Faculty of Mathematics and Natural Sciences, Jenderal Soedirman University. From the results of the Partial Least Square analysis, it was concluded that human resources and facilities and infrastructure had a significant influence on the satisfaction of the practitioners in the Basic Chemistry Laboratory of the Faculty of Mathematics and Natural Sciences, Jenderal Soedirman University. This shows that there must be an increase in the quality of the performance of natural resources and facilities and infrastructure in order to create the desired learning conditions.